САЛЫМДАРДЫ САҚТАНДЫРУ ЖҮЙЕСІН ЖЕТІЛДІРУДІҢ КЕЙБІР ЖОЛДАРЫ - Исаева, Г. К. (Journal of Economic Research & Business Administration, 2015)
Deposit insurance system influence for state development of all financial market. But this system increases the risks of the operation of the commercial banks. In this article researched Deposit insurance models of the different countries in the world. Also there get to improve it: use government Deposit systems with proprietary systems where will be functioned insurance companies.